Pendekatan Adaptive Reuse pada Ruang dan Fasad Bangunan Modernisme 1960an: Antara Preservasi dan Komersialisasi - Trihanondo, Donny (Ideas Publishing, 2024)
This paper discusses adaptive reuse approaches to the spaces and facades of 1960s modernist buildings, with a focus on preservation and commercialization. The aim of this paper is to understand the adaptive reuse approach as a preservation strategy for 1960s modernist buildings, while exploring the relationship between preservation and commercialization. Qualitative methods with interpretivism approach were used to examine research objects which included samples of 1960s modernist buildings including the Hotel Indonesia building, BNI Thamrin Building, Sarinah Thamrin Department Store and Djakarta Theatre. The results of this research are new insights into how to restore the essence of modernist buildings as cultural heritage as well as preservation strategies that also pay attention to the commercialization side.